Conjunctival MicroRNA Expression in Inflammatory Trachomatous Scarring - Derrick, Tamsyn (Public Library of Science, 2013)
PURPOSE: Trachoma is a fibrotic disease of the conjunctiva initiated by Chlamydia trachomatis infection. This blinding disease affects over 40 million people worldwide yet the mechanisms underlying its pathogenesis remain poorly understood. We have investigated host microRNA (miR) expression in health (N) and disease (conjunctival scarring with (TSI) and without (TS) inflammation) to determine if these epigenetic differences are associated with pathology. METHODS: We collected two independent samples of human conjunctival swab specimens from individuals living in The Gambia (n = 63 & 194). miR was extracted, and we investigated the expression of 754 miR in the first sample of 63 specimens (23 N, 17 TS, 23 TSI) using Taqman qPCR array human miRNA genecards. Network and pathway analysis was performed on this dataset. Seven miR that were significantly differentially expressed between different phenotypic groups were then selected for validation by qPCR in the second sample of 194 specimens (93 N, 74 TS, 22 TSI). RESULTS: Array screening revealed differential expression of 82 miR between N, TS and TSI phenotypes (fold change >3, p<0.05). Predicted mRNA targets of these miR were enriched in pathways involved in fibrosis and epithelial cell differentiation. Two miR were confirmed as being differentially expressed upon validation by qPCR. miR-147b is significantly up-regulated in TSI versus N (fold change = 2.3, p = 0.03) and miR-1285 is up-regulated in TSI versus TS (fold change = 4.6, p = 0.005), which was consistent with the results of the qPCR array. CONCLUSIONS: miR-147b and miR-1285 are up-regulated in inflammatory trachomatous scarring. Further investigation of the function of these miR will aid our understanding of the pathogenesis of trachoma.